Semi-active Damping Device Based on Superelastic Shape Memory Alloys. (August 2015) - Silva Lobo, Paulo; Almeida, João; Guerreiro, Luís
Abstract: Repair costs of structures subjected to intense seismic activity are influenced by the maximum and residual displacements they experience. As a result, the relevance of re-centring in seismic protection has been highlighted in recent research involving new materials, of which shape memory alloys stand out, opening up new possibilities in the field of motion control of structures. In this paper, the concept of a new semi-active damping device based on superelastic shape memory alloys, developed in order to surpass some limitations presented by other control solutions, is introduced. Analytical implementation made it possible to assess the new device for control of a single-degree-of-freedom oscillator, simulating the longitudinal behaviour of a bridge, and of a similar model with added fuse, for evaluating its re-centring capacity. The proposed device is capable of significant energy dissipation, similar to linear derivative solutions, and it is also capable of re-centring. The results obtained indicate that the new semi-active device is efficient for seismic protection of structures with nonlinear behaviour. The effects of time-delay on the response of the proposed damper were also evaluated, showing that, for expected values of time-delay, response degradation is not significant.